2020
DOI: 10.1177/0300060519895089
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cell-cycle related and expression-elevated protein in tumor (CREPT) in malignant cervical cancer

Abstract: Objective: To explore the expression of cell-cycle related and expression-elevated protein in tumor (CREPT), cyclin D1, and transcription factor 4 (TCF4) in patients with cervical carcinoma. Methods: This study enrolled 20 patients with cervical cancer and 10 control patients diagnosed with benign cervical lesions undergoing resection at the People's Liberation Army General Hospital from January 2016 to December 2017. Cervical tissues were collected from all patients and their clinical characteristics were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Through genetic analysis, CREPT, p15RS, and RTT103 evolved in the same progenitor cells and participated in cell cycle regulation. Previous studies have found that CREPT is involved in various regulations of transcription, cell cycle, tumorigenesis, and DNA repair [ 3 , 4 ]. CREPT is a cell cycle-related protein.…”
Section: Introductionmentioning
confidence: 99%
“…Through genetic analysis, CREPT, p15RS, and RTT103 evolved in the same progenitor cells and participated in cell cycle regulation. Previous studies have found that CREPT is involved in various regulations of transcription, cell cycle, tumorigenesis, and DNA repair [ 3 , 4 ]. CREPT is a cell cycle-related protein.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of CDK depends on the cyclins that are expressed in the different phases of the cell cycle (13). CDK and cyclins combine to form a cell cycle-dependent complex that regulates the progression of the cell cycle (14), which may eventually affect the formation and development of tumors (15).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, numerous studies have shown that RPRD1B is highly expressed in a majority of solid tumors, where it promotes cell proliferation, tumor growth and progression. Furthermore, its levels correlate with poor prognosis and overall survival ( Li et al, 2018 ; Liu et al, 2019 ; Lu et al, 2012 ; Ma et al, 2020 ; Ma et al, 2017 ; She et al, 2014 ; Wang et al, 2014b ; Wen et al, 2020 ; Yin et al, 2019 ; Zhang et al, 2018 ; Zheng et al, 2016 ). RPRD proteins can modulate CTD Serine 5 (Ser5) and Ser7 phosphorylation levels, likely through the recruitment of the phosphatase RPAP2 ( Ni et al, 2011 ; Ni et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%